2021
DOI: 10.1111/jocd.14528
|View full text |Cite
|
Sign up to set email alerts
|

Updated review on prognostic factors in mycosis fungoides and new skin lymphoma trials

Abstract: Background: Ten-year survival rates in mycosis fungoides (MF) broadly varies, however, there is no standardized prognostic index available. This is presumably due to low prevalence, heterogeneity, and diagnostic challenges in MF. Recent studies have focused on identifying objective prognostic indices by using different parameters for survival determinants. The Cutaneous Lymphoma International Prognostic Index (CLIPI) and the Prospective Cutaneous Lymphoma International Prognostic Index (PROCLIPI) represent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Pruritus is a frequently overlooked but impactful symptom in MF patients, affecting approximately 50% of individuals. 18 This symptom adversely affects sleep, daily activities and can lead to public embarrassment due to scratching. 3,4 In our study, we found the presence of pruritus in MF patients to be at a rate of 50.6%, and we observed a significantly higher DLQI score in MF patients with pruritus compared to those without pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…Pruritus is a frequently overlooked but impactful symptom in MF patients, affecting approximately 50% of individuals. 18 This symptom adversely affects sleep, daily activities and can lead to public embarrassment due to scratching. 3,4 In our study, we found the presence of pruritus in MF patients to be at a rate of 50.6%, and we observed a significantly higher DLQI score in MF patients with pruritus compared to those without pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…Guenova 1 | P. L. Ortiz-Romero 2 | B. Poligone 3 | C. Querfeld 4 sex, older age (>60 years), presence of plaques and lymph node stage >N1 and/or Nx may also portend poor survival. 14 MF has a significant impact on a patient's health-related quality of life (QoL). Physical symptoms, such as pain, pruritus and alopecia, and other factors such as insomnia, anxiety, shame, embarrassment and depression can interfere with work, school and other daily activities.…”
Section: Mechanism Of Action Of Chlormethine Gel In Mycosis Fungoidesmentioning
confidence: 99%
“…Although patients with stage IA MF generally have a normal life expectancy, 12 the prognosis for advanced disease is poor, with one study reporting a median survival of approximately 5 years and a 5‐year survival rate of just 52% 13 . Disease prognosis is influenced by many factors, which are not yet fully defined, but the strongest known risk factors for poor survival are advanced tumour stage and presence of extracutaneous disease; male sex, older age (>60 years), presence of plaques and lymph node stage >N1 and/or Nx may also portend poor survival 14 …”
Section: Introductionmentioning
confidence: 99%
“…CTCL accounts for approximately 65–75% of all primary cutaneous lymphomas (CL) and constitutes a group of malignancies with heterogeneous clinical, histopathological, and immunophenotypic characteristics [ 1 , 2 , 3 , 4 ]. The incidence rate of CTCL has increased in the last decade partly due to better diagnosis of the disease and it may range from six to nine per million people when comparing African Americans and Caucasians, respectively [ 5 , 6 , 7 ]. Classical subtypes of CTCL include mycosis fungoides (MF) and Sézary syndrome (SS), which manifest male predominance with an approximate 2:1 male to female ratio and mostly affect elderly people with a median age at diagnosis of 50–60 years [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in about 25–30% of early-stage patients, the disease may progress into infiltrating plaques, ulcerated tumors (designated as T3), and blood/systemic involvement, and the 5-year OS is reduced to 18% (stage IVB) [ 8 , 11 ]. As briefly mentioned above, CD30+ LPDs account for the second most common CTCL subtype after MF, which histologically presents large CD30+ tumor cells and is characterized by an indolent course and a favorable prognosis [ 5 ]. While large cell transformation (LCT) is defined by CD30− or CD30+ large cells, with a cell size fourfold larger than a small lymphocyte, that exceeds 25% of the tumor infiltrate, this histologic feature is identified in only 25–50% of MF patients with advanced stage [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%